Islamic commitment of female characters in ‘Ibarat Al-Hubb (VERSES OF LOVE) by Habiburrahman El-Shirazy - Muhammad Anwar Ahmad,; Ilham Ramadhan,; Mohd Shahrizal Nasir, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study examines the female characters in Verses of Love by Habiburrahman El Shirazy of Indonesia from the perspective of literary criticism and Islamic literature. This research analyses the dimensions of the female characters and the writer’s methods of characterization as well as the Islamic values in both novels. This study investigates the themes and conflicts in the novel to examine the dimensions of the female characters and the methods of characterization. In sum, this novel is Islamic novel which features different characteristic of women involved in conflicts. The novel showed a pious man as the main character facing challenges in his relationships with women from Egypt, Turkey, and Indonesia. Finally, the researchers concludes that the novelist has successfully depicted various female characters, and this proves that the novelist is innovative.